Ecological analysis of helminth fauna of wild artiodactyles (Mammalia: artiodactyla) in Karakalpakstan - F. J. Akramova; M. Sh. Toremuratov; U. A. Shakarbaev; L. A. Rakhmonova; D. A. Azimov; L. U. Erkinova (Российский паразитологический журнал, 2020)
The purpose of the research is studying current fauna of helminths in wild artiodactyls and analysis of their ecological relationships with populations of representatives of the Artiodactyla in biogeocenoses of Karakalpakstan.Materials and methods. Wild populations of artiodactyls were studied in 2016–2020 in the ecosystems of the Kyzyl Kum, Ustyurt and the lower reaches of the Amu Darya, including the drained bottom of the Aral Sea. Some killed animals (the saiga, Persian gazelle, and Bokharan deer) seized from poachers, as well as those killed by predators and feral dogs in the sanctuaries and reserves of Karakalpakstan were used to collect helminthological material. Wild boars were examined after shooting during the hunting season. A total of 11 saigas, 13 Persian gazelles, 7 Bokharan deer and 16 wild boars, and 213 fecal samples from these animals were examined. The studies were carried out using generally accepted methods of dissection (Skryabin, 1928; Ivashkin et al., 1971) and ovoscopy of animal feces. For a comparative analysis of helminth fauna of the study animals, we used previously collected (1959–1978) parasites from the wild boar, saiga, Persian gazelle and Bokharan deer in Karakalpakstan.Results and discussion. We have found that the fauna of the Artiodactyla is represented by the following 5 species in the biogeocenosis of Karakalpakstan: Sus scrofa nigripes Blan., Cervis elaphus bactrianus Lydek., Gazella subgutturosa Gueld., Saiga tatarica Linn., and Ovis orientalis arcal Gmel., in which we identified 26 helminth species classified as Cestoda, Trematoda and Nematoda. Cestodes are represented by 6 species, trematodes by 2 species, and nematodes by 18 species. The helminth species composition of the study animals is 14 species in pigs, 11 species in Bokharan deer, 13 species in saigas and 14 species in Persian gazelles. Representatives of the genera Taenia, Echinococcus, Fasciola, Schistosoma, Gongylonema and Setaria are common to these animal species. By nature of the biological cycle, the helminths of the study artiodactyls recorded by us can be divided into two groups: monoxenous and heteroxenous. Monoxenous parasites include representatives of the Trichocephalidae (3 species), Trichostrongylidae (2 species), Dictyocaulidae (2 species), Syphaciidae (1 species), and Ascarididae (1 species), whose life cycles proceed without changing hosts. Eighteen species of representatives of cestodes (6 species), trematodes (2 species) and nematodes (10 species) are developed with the involvement of intermediate hosts.